Person-centred approach to counseling : indicators of personal growth experienced by Malay clients - Mohamad, Mardiana; Abu Samah, Asnarulkhadi (Pearson, 2012)
The emergence of the themes suggests that the Malay clients in the study did move in the direction of personal growth and maturity in the non-directive, egalitarian person-centred counselling. The flow of emotion experienced by clients indicated that, in the safe climate of person-centred counselling, where the client' positive and negative feelings were accepted and understood accurately by the counsellor, a tremendous sense of relief and comfort were felt by the client, as found by Watson (2002).